Biological influences on criminal behavior - Anderson, Gail S. (Gail Scott) (Boca Raton, Fla. : CRC Press, 2007)
Drawing on recent research in genetic background, hormone and neurotransmitter levels, diet, and physical insults like brain trauma, this book integrates the biological view with mainstream social, psychological, and environmental views to suggest a new way of studying criminality and to gain some positive and useful explanations of criminal behavior. The book helps the criminologist navigate a new area of study, one with its own complexities and challenges. The author does not suggest that biology plays the major role, but something vital can be discovered when all factors related to the cause of crime are assessed, including biology.
Introduction to biology and crime -- Basic biological concepts -- Genetic concepts -- Introduction to genetic predispositions for behavior -- Evidence for genetic predispositions for criminogenic behavior -- Hormonal effects on behavior -- Pregnancy and the effects of birth -- Brain chemistry -- Organic brain dysfunctions: pt. I -- Organic brain dysfunctions: pt. II -- Diet, toxins, and food additives.
OCLC-licensed vendor bibliographic record.
Keywords: Criminal behavior; Human biology -- Social aspects; Criminal behavior -- Genetic aspects; Sociobiology; Criminology; SOCIAL SCIENCE -- Criminology